PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP PERUBAHAN HARGA SAHAM (Penelitian pada Saham Perusahaan Pertambangan Milik Pemerintah yang Go Public Di BEI Tahun 2003 -2012) - Hanggara, Agie (Equilibrium, 2015)
Based on the estimation result sindicate that simultaneous Liquidity Ratio (CR), Solvency Ratio(DER), Market Value Ratio(PER) and the profitability ratio (ROA) significant effect on changes instock prices. And partially variable Solvency Ratio (DER), Market Value Ratio(PER) and the profitability ratio (ROA) has asignificant positive effecton stock price changes, while for Variable Liquidity Ratio (CR) is nota significant positive effecton stock price movements Mining company Government Owned go public in Indonesia Stock Exchange (BEI) in the period 2003 to 2012 obtained from this study adjusted R Square of 0.609084, this means that 60.91% of the dependent variable can be explained by the independent variables and the remainderis equal to 39.09% explained by variables other than the equation.